MOTIF PETANI DALAM MEMILIH PASAR (KASUS DI SUB TERMINAL AGRIBISNIS TERPADU TANIRAN KABUPATEN HULU SUNGAI SELATAN) - Yandi Aulia Rahman; Reza Safitri; Edi Dwi Cahyono (Sepa, 2020)
The development of Agribusiness Sub Terminal aims to increase the added value of farmers, by cutting the long chain of distribution, started from producer farmers, collector traders, large traders to consumers. However, the extension of the chain still occurs, where farmers prefer to sell their agricultural products to intermediary traders than to the Integrated Agribusiness Sub Terminal of  Taniran. The purpose of this research is to find out why farmers prefer to sell agricultural products to intermediary traders than to Integrated Agribusiness Sub Terminal of Taniran. The research approach uses qualitative case study design and informant determination techniques purposively. The results of the research found that there are four reasons why farmers sell their vegetables to intermediary traders, namely: (a) family and social relationship, (b) limited capital, (c) guaranteed marketing of vegetables in a fluctuated price, (d) assistance in the process of sorting, packing and transporting.